Design and development of an automated spirulina (Arthrospira platensis) algae cultivator - Mariñas II, Miguel Q.; B. Enojas, Mark Joseph; Balolong, Daryll C.; B. Correa, Charissa Zandra; C. Roldan, Lemmuel Keith; Teves, Mark Lester; Dela Cruz, Christian Mari (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The cultivation of algae has gotten more attention from algae enthusiasts who have seen the benefits of algae in many uses. To maximize productivity, the parameters for growth of this algae must be controlled, such as pH, turbidity, light intensity, and the mixture solution for optimal growth. In this paper, an automated spirulina algae cultivator is designed and developed in a small-scale pond to replace the existing manual process. The system developed is composed of compact and modular cultivation unit, ph sensor, water level sensor, turbidity sensor, light intensity sensor, and motor actuators for mixing solutions. Each parameter was controlled individually in an on-off control system. A simple nutrient addition program (SNAP) solution is also used for better growth productivity by maximizing its nutrient contents. The pH is maintained at 9 to 12 for a healthy biomass output. Daily weight measurement was conducted using an analytical balance to monitor its growth. Using the developed prototype recorded a 33% higher rate of productivity over the manual process. This setup can potentially be used as a model for mass production of spirulina algae.